Constraintson the double-parton scattering cross section from same-sign W boson pair production in proton-proton collisions at root s=8TeV - Sirunyan, A. M. (2018)
A first search for same-sign WW production via double-parton scattering is performed based on proton-proton collision data at a center-of-mass energy of 8TeV using dimuon and electron-muon final states. The search is based on the analysis of data corresponding to an integrated luminosity of 19.7 fb(-1). No significant excess of events is observed above the expected single-parton scattering yields. A 95% confidence level upper limit of 0.32 pb is set on the inclusive cross section for same-sign WW production via the double-parton scattering process. This upper limit is used to place a 95% confidence level lower limit of 12.2mb on the effective double-parton cross section parameter, closely related to the transverse distribution of partons in the proton. This limit on the effective cross section is consistent with previous measurements as well as with Monte Carlo event generator predictions.